(untitled) (Teología, 2020)
The article presents the doctoral thesis which has been defended by its writer in December 2016, at the Faculty of Theology Santa María de los Buenos Aires belonging to the Pontifical Catholic University of Argentina, which is under Friar Dr. Jorge A. Scampini op.’s direction. Its title is "The Church’s unity. Its development within the biographical-ecclesiology by John Henry Newman", is being justified by two topics: developing unity and biographical ecclesiology. The current thesis aims, on the one hand, to outstrip a static concept of the Church unity which has been dom- inating in the Catholic ecclesiology since the catholic Counter-Reformation and has also prevented the communication and dialogue between the different churches. On the other hand, it also aims to discover the development of the idea of unity within the existential framework of Newman’s life, thus showing the similarities and paradoxes that have been established in the two confessional periods during which the author (an Anglican-Catholic) has lived.